Experience and Eternity in Spinoza - Moreau, Pierre-François, 1948- (Spinoza studies., 2021)
Through a detailed study of Spinoza's concept of 'experience', Moreau shows how Spinoza extends the power of reason to capture the singularity of individuals: their lives, languages, passions and societies.